2012
DOI: 10.1007/s00125-012-2774-z
|View full text |Cite
|
Sign up to set email alerts
|

Volume of supervised exercise training impacts glycaemic control in patients with type 2 diabetes: a systematic review with meta-regression analysis

Abstract: Aims/hypothesis Supervised exercise programmes improve glycaemic control in type 2 diabetes, but training characteristics associated with reduction in HbA 1c remain unclear. We conducted a systematic review with meta-regression analysis of randomised clinical trials (RCTs) assessing the association between intensity and volume of exercise training (aerobic, resistance or combined) and HbA 1c changes in patients with type 2 diabetes. Methods Five electronic databases were searched to retrieve RCTs of at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 57 publications
8
143
0
7
Order By: Relevance
“…However, these probabilities should not be overinterpreted, particularly since they are not very large (not close to 80-90%). A dose-response meta-regression analysis by Umpierre et al [48] summarised the effects of CT, AET and RT on glycaemic control in patients with type 2 diabetes and concluded that the reduction in HbA 1c was associated with exercise frequency in supervised AET, and with the weekly volume of RT in supervised CT. Regarding the optimal dose, the authors speculated that there should be a minimal amount of AET (33 min per session) to elicit the effects of highvolume RT in CT [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, these probabilities should not be overinterpreted, particularly since they are not very large (not close to 80-90%). A dose-response meta-regression analysis by Umpierre et al [48] summarised the effects of CT, AET and RT on glycaemic control in patients with type 2 diabetes and concluded that the reduction in HbA 1c was associated with exercise frequency in supervised AET, and with the weekly volume of RT in supervised CT. Regarding the optimal dose, the authors speculated that there should be a minimal amount of AET (33 min per session) to elicit the effects of highvolume RT in CT [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gando et al (26) showed that light-intensity physical activity was inversely associated with insulin resistance in elderly Japanese women. Another study demonstrated that the frequency of exercise is an influential factor more likely to underlie the beneficial effects of aerobic training, suggesting that the repetition of exercise sessions may be more important than longer or more intense sessions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Se encontró una reducción significativa en las cantidades de HbA1c (−0,73 %; IC95 %: −1,06 % a −0,40 %). Una segunda revisión sistemática de la literatura del mismo autor [30] demostró cómo a mayor frecuencia de sesiones de ejercicio aeróbico a la semana se presentaban mayores reducciones en las concentraciones de HbA1c; también se encontró una disminución del 0,39 % adicional por cada sesión de ejercicio. Cabe recalcar que solamente aconsejar actividad física no tiene un efecto significativo en la HbA1c.…”
Section: Ejercicio Físicounclassified